Characteristics of Nanopowders Produced by Electrical Explosionof Tin–Lead Alloy Conductors in Air; Inorganic Materials: Applied Research; Vol. 2, № 12 - Ilyin A. P. Aleksandr Petrovich (2011, 2011)
The article discusses the investigations into the phase and chemical composition of nanopowdersproduced upon electrical explosion of conductors made of tin–lead alloy (POS61) in air. It is demonstratedthat, in the course of electrical explosion and subsequent cooling of the dispersion products, there occurs aslight enrichment (by 3–6 at %) of the surface and subsurface layers of the powder particles with lead in comparison with its content in the initial alloy.